Gambaran Kebermaknaan Hidup pada Pria dengan Perilaku Homoseksual - Natasya Audia Feirly; Merly Erlina (Jurnal Penelitian Kualitatif Ilmu Perilaku, 2021)
Homosexuals are still considered taboo and frightening for a majority heterosexual Indonesian society. During their lives, homosexuals have a meaning in their lives, what has become their choice now does not just happen, but there are life experiences that have been lived and life lessons that have their own meaning. This study aims to know and understand the meaning of life in men with homosexuals behavior in Tangerang. This research method is qualitative with case study approach. Data collection techniques using snowball sampling. The number of subjects willing to be participants in the study was three people with the criteria, two of whom were bisexual and one was gay. The results showed that the three subjects found the meaning of life from the aspects specified. All three had uniqueness, activities that guided the meaning of life, believing in the existence of God and carrying out worship. Two out of three subject have experienced tragic events that have passed through during life. With homosexuals behavior, all three can interpret life and have a strong belief in survival among the majority of heterosexuals, even the three subjects also have jobs and education equivalent to heterosexuals..